Potensi Jus Kombinasi Daging Kelapa (Cocos nucifera) dan Daging Putih Semangka (Citrullus lanatus) sebagai Modalitas Preventif Dislipidemia: The Potential of a Combination Juice of Coconut Flesh (Cocos nucifera) and White Flesh of Watermelon (Citrullus lanatus) as a Preventive Modality of Dyslipidemia - Hasnan Habib Afifudin; Muhammad Malik Fajar; Muhammad Hanif Al As’ad Budiyanto; Daeng Catur Dharma Rahmatullah; Andika Danendra Widyadana; Prabaswara Ulung Linuwih; Akmal Widi Rakhmanto; Miranti Dewi Pramaningtyas (Universitas Airlangga, 2023)
Background: Dyslipidemia is a condition in which lipid levels are abnormal. Dyslipidemia can lead to diseases such as atherosclerosis and coronary heart disease. Coconut flesh and white flesh of watermelon are known to have antioxidant compounds that can prevent dyslipidemia. Objectives: This study aimed to prove the potential of combining coconut flesh and watermelon flesh intervention to inhibit metabolic parameters in dyslipidemic conditions. Methods: This study was an experimental study with a post-test only with a control group design involving five groups of 25 Wistar mice treated with dyslipidemia induction using quail egg yolk. Treatment followed by the intervention of coconut flesh juice, white flesh of watermelon juice, or a combination of both, and one control group with induction of dyslipidemia with quail egg yolk followed by aqueous intervention. The intervention duration is 28 days, with a blood draw carried out on the 29th day. The lipid profile test was carried out using blood plasma. Data analysis begins with the Shapiro-Wilk test and a one-way ANOVA test. Results: There were no significant differences in the result of LDL, triglyceride, and total cholesterol between groups (P>0.05) and significant differences in HDL between groups (p< 0.05). Conclusions: The intervention of watermelon white flesh juice and coconut flesh significantly affected HDL levels but did not significantly affect dyslipidemic rats' LDL, triglyceride, and total cholesterol.